Localisation in the Context of UK Government Engagement With the Humanitarian Reform Agenda - Goodwin, Ellen; Ager, Alastair (Frontiers in Political Science, 2021)
Localisation is a key element of the humanitarian reform agenda. However, there are continuing debates regarding its form and emphasis, linked to understandings of the local, the role of the state and the implications for interpretation of humanitarian principles of “de-internationalised” humanitarian response. This paper considers UK engagement with the localisation agenda, particularly through examination of the policies and programmes of the Department for International Development (DFID). The UK was a major contributor to dialogue on localisation at the World Humanitarian Summit of 2016 and has subsequently shown strong support for Grand Bargain commitments and implementation of a larger proportion of programmes involving cash transfers. Overall, however, advance on this agenda has been limited. The paper notes three major areas of constraint. First, logistical concerns have frequently been noted, particularly with respect to tasks such as procurement and financial monitoring. This has limited the engagement of many local actors lacking organisational capacity in these areas. Second, conceptual ambiguity has also played a significant role. Localisation is poorly theorised, and the roles, functions and capacities—beyond procurement of supplies and emergency technical assistance—that local actors may be able to fulfil far more effectively than international ones are not frequently addressed. Narrowly framed understandings of principles such as independence and impartiality, for instance, appear to severely limit confidence in engaging with local religious actors. Third, political considerations appear to have increasingly limited the space for more radical interpretations of the implications of localisation. Successive UK Secretaries of State for International Development have defended the commitment to a fixed proportion of Gross National Income (GNI) for development assistance based on strong public support for UK aid expenditure to reflect national interests and values. In this context, there are few clear political incentives to cede power over decision-making regarding UK Overseas Development Assistance (ODA) to national and local actors in a manner required for fundamental localisation of humanitarian response. Even where there is a clear potential UK interest—for example, bolstering capacity of local actors in contexts vulnerable to humanitarian emergency to avert more costly emergency response—the public perception of capacity strengthening (compared to life-saving humanitarian actions) mitigates against such moves in a climate of contested public spending. The establishment of a merged Foreign Commonwealth and Development Office in 2020 signals the likelihood of a reframing of localisation. While some advancement in terms of some logistical and conceptual barriers may be anticipated, issues of both national interest and public perceptions of national interest seem likely to continue to constrain a more radical implementation of localisation, particularly with current suspension of the commitment to spend 0.7% of GNI on ODA.